National Geographic bucket list family travel : share the world with your kids on 50 adventures of a lifetime - Gee, Jessica (National Geographic, 2024)
The author shares her best tips and tricks for breaking out of your comfort zone and experiencing the world with your kids. Along with how to pack, plan, and budget, she offers her best advice for surviving a plane ride with a toddler, tackling jet lag and naptimes, and finding childcare abroad. Includes 50 itineraries to destinations around the globe.--Adapted from back cover.